HDAC8: A Promising Therapeutic Target for Acute Myeloid Leukemia - Spreafico, Marco; Gruszka, Alicja M.; Valli, Debora; Mazzola, Mara; Deflorian, Gianluca; Quintè, Arianna; Totaro, Maria Grazia; Battaglia, Cristina; Alcalay, Myriam; Marozzi, Anna; Pistocchi, Anna (Frontiers in Cell and Developmental Biology, 2020)
Histone deacetylase 8 (HDAC8), a class I HDAC that modifies non-histone proteins such as p53, is highly expressed in different haematological neoplasms including a subtype of acute myeloid leukaemia (AML) bearing inv(16). To investigate HDAC8 contribution to haematopoietic stem cell maintenance and myeloid leukaemic transformation, we generated a zebrafish model with Hdac8 overexpression and observed an increase in haematopoietic stem/progenitor cells, a phenotype that could be reverted using a specific HDAC8 inhibitor, PCI-34051 (PCI). In addition, we demonstrated that AML cell lines respond differently to PCI treatment: HDAC8 inhibition elicits cytotoxic effect with cell cycle arrest followed by apoptosis in THP-1 cells, and cytostatic effect in HL60 cells that lack p53. A combination of cytarabine, a standard anti-AML chemotherapeutic, with PCI resulted in a synergistic effect in all the cell lines tested. We, then, searched for a mechanism behind cell cycle arrest caused by HDAC8 inhibition in the absence of functional p53 and demonstrated an involvement of the canonical WNT signalling in zebrafish and in cell lines. Together, we provide the evidence for the role of HDAC8 in hematopoietic stem cell differentiation in zebrafish and AML cell lines, suggesting HDAC8 inhibition as a therapeutic target in haematological malignancies. Accordingly, we demonstrated the utility of a highly specific HDAC8 inhibition as a therapeutic strategy in combination with standard chemotherapy.